2012
DOI: 10.1111/j.1747-0080.2012.01620.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving opportunities for food service and dietetics practice in hospitals and residential aged care facilities

Abstract: Aim:  Food is a phenomenon that everyone has an opinion on because eating is a frequent, often social occurrence, and as such the importance of mealtimes can be undervalued in healthcare settings. Some staff may not share our concerns about suboptimal dietary intakes as they assume that nutritional status will improve as people feel better. However, the provision and consumption of an appealing and adequate diet is a critical aspect of holistic health care. This review examines the role of dietitians in food s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
(96 reference statements)
0
13
1
Order By: Relevance
“…The meal budget, food regulations, management support and staff attitudes were all identified as local constraints. Other authors have reported similar views by chefs and cooks in ACF and advocate for similar system‐wide changes . The agency of foodservice providers to enact change is impacted upon by multiple levels of influence, including those at the personal, social and environmental level .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The meal budget, food regulations, management support and staff attitudes were all identified as local constraints. Other authors have reported similar views by chefs and cooks in ACF and advocate for similar system‐wide changes . The agency of foodservice providers to enact change is impacted upon by multiple levels of influence, including those at the personal, social and environmental level .…”
Section: Discussionmentioning
confidence: 81%
“…Adequate nutrition is essential for older adults’ health and it is necessary to optimise the food service system in ACF as residents are dependent on these services for the provision of their meals . Barriers to food service include a lack of prioritisation of food service at a funding level, a lack of well‐trained knowledgeable professionals and food service staff and a lack of national food and nutrition regulation, while juggling the variety of special dietary needs of residents …”
Section: Introductionmentioning
confidence: 99%
“…Early experiences as a student or new graduate were seen as highly influential on whether dietitians chose to pursue careers in management or foodservice . Strong role models are essential to inspire future leaders and engage new dietitians in foodservice . It has been suggested that additional advanced training programmes may be needed to build the individuals’ confidence in their abilities to manage .…”
Section: Foodservice Management and Leadership Trainingmentioning
confidence: 99%
“…Substantial evidence in foodservice satisfaction measurement in both the hospital and residential aged care sectors has been developed by Australian dietitians and applied consistently in international contexts, whilst in this issue we publish a meal quality audit tool . Walton also argues that further evidence regarding cost‐benefit and cost‐effectiveness is essential to foodservice dietetics and that significant prospects exist for dietitians to extend career opportunities within foodservice departments of hospitals . Acute care hospital research dominates the published foodservice literature, whilst gaps in the evidence, particularly in some clinical cohorts, remain.…”
Section: Foodservice Researchmentioning
confidence: 99%
See 1 more Smart Citation